Financial Management Impact on Performance Reports in Borrower Multisupplier and Consultancy LTD, Kigali Rwanda - Dusabeyezu, Seraphin; Safari, Ernest (Journal of Finance and Accounting, 2023)
This study aimed to analyze the impact of financial management on performance reports in Borrower Multisupplier consultancy (BMSC Ltd, Kigali Rwanda). The research uses a descriptive survey design and quantitative method, with 133 employees and 121 sellers as a sample size. Data was collected using structured questionnaires and analyzed using SPSS software version 21. The Cronbach alpha coefficient formula was used for reliability and validity. The results show that quality financial reporting contributes significantly to performance reports, with a high positive correlation between these two factors. The use of ratio analysis is also important, with a high positive correlation between ratio analysis and performance reports. Internal control is also crucial, with a high positive correlation between internal control and performance reports. The ANOVA results show a significant relationship between financial management and performance reports in Borrower Multisupplier and Consultancy Ltd, Kigali Rwanda. The researcher concludes that financial management contributes to performance reports and recommends that companies develop financial management techniques that contribute successfully to their company’s performance reports. The findings are presented and interpreted using frequencies and tables. The findings suggest that financial management plays a crucial role in enhancing performance reports and should be considered in the development of financial management strategies for borrower and multisupplier companies. Keywords: Financial management, Performance reports, Borrower Multisupplier, Consultancy, Rwanda